Academic Patents and Entrepreneurial Intention: To What Extent Are Other Knowledge Transfer Mechanisms Affected in a Mexican University? - Calderón, María Guadalupe; Perez, Pilar (Journal of Evolutionary Studies in Business, 2021)
Abstract: This research aims to expand the explanations about the debate on academic entrepreneurship and other knowledge transfer mechanisms, to respond to what extent entrepreneurial intention affects the diffusion and dissemination of knowledge in a Mexican university. The lack of indicators of commercial activity, leads us to propose the analysis of a pre-commercial stage of technology that we call entrepreneurial intention. After the literature review, we present a database of academic inventors in patents granted to the university, identifying patenting with an entrepreneurial intention, following Lomas (1993) knowledge transfer taxonomy. Data about publications and received citations by academic inventors is also considered for knowledge diffusion; as well as the supervision of end-of-degree projects in undergraduate and graduate studies; before and after the patent was granted, for knowledge dissemination. Using a binomial model, we estimated two data sets, one for the period 1984-2000 and the second for 2001-2020. Our findings reveal, an average increase of 60% in the number of patents obtained. We also found that the characteristics of the research group are significant in both models, but in the 2001-2020 period it is more important to integrate foreign inventors than patenting with firms, the dissemination of knowledge is more significant and has greater importance in the model. To respond to what extent entrepreneurial intention affects the diffusion and dissemination of knowledge, greater attention should be paid to the diffusion of knowledge since in both models the variable that represents publications after patenting is not significant. The explanation about the dissemination of knowledge improves substantially from one period to another.
Code: Journal of Evolutionary Studies in Business Number: 2
Keywords: Business history in Latin America